Structure, magnetic and magnetoresistive properties of composite materials based on ferromagnetic metals and alloys with different types of dielectric matrix - Pazukha, I.M.; Shchotkin, V.V.; Shkurdoda, Yu.O. (Успехи физики металлов, 2019)
A literary review of the experimental results concerning phase state and crystal structure, magnetoresistive and magnetic properties of the thin-film composite materials formed on the base of granules of ferromagnetic Co metal or FexCo₁₋x alloy embedded into the insulator matrix (SiO, SiO₂, Al₂O₃) via different discovery methods is presented. As shown, the value of magnetoresistance, character of its field dependences and magnetic characteristics depend on the concentration and size distribution of ferromagnetic granules. At the specified conditions, the perpendicular anisotropy can be realized in the structures as ferromagnetic granule–insulator matrix; the reasons of such anisotropy are analysed. Представлено літературний огляд експериментальних результатів стосовно структурно-фазового стану, магнеторезистивних і магнетних властивостей тонкоплівкових композитних матеріалів, сформованих на основі ґранул феромагнетного металу Co або стопу FexCo₁₋x, втілених у діелектричну матрицю (SiO, SiO₂, Al₂O₃) шляхом використання різних метод одержання. Показано, що величина магнетоопору, характер його польових залежностей і магнетні характеристики залежать від концентрації та розподілу за розмірами феромагнетних ґранул. За певних умов у структурах типу феромагнетна ґранула–діелектрична матриця може бути реалізованою перпендикулярна анізотропія, найбільш ймовірні причини виникнення якої проаналізовано. Представлен литературный обзор современных экспериментальных результатов относительно структурно-фазового состояния, магниторезистивных и магнитных свойств тонкоплёночных композитных материалов, сформированных на основе гранул ферромагнитного металла Co или сплава FexCo₁₋x, внедрённых в диэлектрическую матрицу (SiO, SiO₂, Al₂O₃) при использовании разных методов получения. Показано, что величина магнитосопротивления, характер его полевых зависимостей и магнитные характеристики зависят от концентрации и распределения по размерам ферромагнитных гранул. При определённых условиях в структурах типа ферромагнитная гранула–диэлектрическая матрица может быть реализована перпендикулярная анизотропия, наиболее вероятные причины возникновения которой проанализированы.